Fluoride‐Free 2D Niobium Carbide MXenes as Stable and Biocompatible Nanoplatforms for Electrochemical Biosensors with Ultrahigh Sensitivity. Issue 24 (9th November 2020) - Song, Menglin; Pang, Sin‐Yi; Guo, Feng; Wong, Man‐Chung; Hao, Jianhua
Abstract: Recently, 2D niobium carbide MXene has drawn vast attention due to its merits of large surface area, good metallic conductivity, and tunable band gap, making it desirable for various applications. However, the usage of highly toxic fluoride‐containing etchant and quite long etching time in the conventional synthesis route has greatly hindered further exploration of MXene, especially restricting its biomedical application. Herein, novel fluoride‐free Nb2 CT x nanosheets are prepared by a facile strategy of electrochemical etching (E‐etching) exfoliation. Taking advantage of rapid aluminum clearance, excellent chemical stability, and biocompatibility from the MXene by E‐etching, fluoride‐free Nb2 CT x /acetylcholinesterase‐based biosensors are constructed for phosmet detection with the limit of detection down to 0.046 ng mL −1 . The fabricated Nb2 CT x ‐based biosensor is superior to the counterpart from hydrofluoric acid‐etched Nb2 CT x, indicating that fluoride‐free MXene can enhance the enzyme activity and electron transfer in the biosensor. The results prove that the fluorine‐free MXene shows promise for developing biosensors with high performance of ultrahigh sensitivity and selectivity. It is highly expected that the fluoride‐free MXene as a stable and biocompatible nanoplatform has great potential to be expanded to many other biomedical fields. Abstract : Fluoride‐free Nb2 CT x nanosheets are prepared by a facile strategy of electrochemical etching and are engineered into an enzymebased nanoplatform to achieve a detection limit of 0.046 ng mL −1 for phosmet detection, outperforming the counterpart of hydrofluoric acid (HF) etched Nb2 CT x . The results prove that the fluorine‐free MXene can be used in biosensors with ultrahigh sensitivity and selectivity.